1987
DOI: 10.1093/clinchem/33.2.313
|View full text |Cite
|
Sign up to set email alerts
|

Transient hyperphosphatasemia of infancy and early childhood: clinical and biochemical features of 21 cases and literature review.

Abstract: Clinical and biochemical features of transient hyperphosphatasemia of infancy and early childhood are reviewed in 21 patients we have studied and in a further 93 cases reported in the literature. The diagnosis is suggested by the finding of an increased activity of alkaline phosphatase (EC 3.1.3.1) in plasma, typically more than fivefold the adult upper reference limit, in a child under five years of age, without evidence of liver or bone disease. The condition is confirmed by the presence of a characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
33
0
8

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 0 publications
6
33
0
8
Order By: Relevance
“…The length of abnormal ALP values and the benign outcome of our patients are similar to what is reported in the literature. 3,4,6,10,11,14,17,21,29 2 years of age or younger, which is also consistent with the literature. 5,7,10,11,13,16,19 The main limitation of the study is its retrospective nature which limited our ability to control the clinical investigation and ensure appropriate follow-up and timing of laboratory studies.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The length of abnormal ALP values and the benign outcome of our patients are similar to what is reported in the literature. 3,4,6,10,11,14,17,21,29 2 years of age or younger, which is also consistent with the literature. 5,7,10,11,13,16,19 The main limitation of the study is its retrospective nature which limited our ability to control the clinical investigation and ensure appropriate follow-up and timing of laboratory studies.…”
Section: Discussionsupporting
confidence: 92%
“…These finding are consistent with previous studies and support the theory of an infectious agent as a possible etiology for TH. 4,14,15,[18][19][20][21] Mahy et al have shown that Riley virus-infected mice decrease enzyme clearance probably through the inhibition of the reticuloendothelial system. 22 Nevertheless, this decreased enzyme clearance has not been shown for ALP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations